Dalla Vía, Alberto R., Derecho Electoral. Teoría y práctica, Buenos Aires, Rubinzal Culzoni, 2021, 472 pp. - Urquiza Rueda, Santos (2022)
Fil: Urquiza Rueda, Santos. Pontificia a Universidad Católica Argentina; Argentina